2013
DOI: 10.1097/jto.0b013e3182a4713e
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotection of Lung Tissue by Soy Isoflavones

Abstract: Introduction Radiation-induced pneumonitis and fibrosis have restricted radiotherapy for lung cancer. In a pre-clinical lung tumor model, soy isoflavones showed the potential to enhance radiation damage in tumor nodules and simultaneously protect normal lung from radiation injury. We have further dissected the role of soy isoflavones in the radioprotection of lung tissue. Methods Naïve Balb/c mice were treated with oral soy isoflavones for 3 days before and up to 4 months after radiation. Radiation was admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 33 publications
4
37
0
Order By: Relevance
“…We have previously demonstrated that soy isoflavones protect against radiation-induced pneumonitis and fibrosis in naïve mice and xenografted lung tumor-bearing mice (1012). In naïve mice, soy isoflavones given preradiation and postradiation reduced radiation injury to skin and hair follicles, protected respiratory function, and decreased inflammatory infiltrates and fibrosis (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that soy isoflavones protect against radiation-induced pneumonitis and fibrosis in naïve mice and xenografted lung tumor-bearing mice (1012). In naïve mice, soy isoflavones given preradiation and postradiation reduced radiation injury to skin and hair follicles, protected respiratory function, and decreased inflammatory infiltrates and fibrosis (12).…”
Section: Introductionmentioning
confidence: 99%
“…In naïve mice, soy isoflavones given preradiation and postradiation reduced radiation injury to skin and hair follicles, protected respiratory function, and decreased inflammatory infiltrates and fibrosis (12). Significant decreases in pneumonitis, vascular damage, and fibrosis were also observed in lung tumor-bearing mice treated with soy isoflavones and radiation (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Genistein is well tolerated, easily administered and it has recently been reported that soy isoflavones such as genistein act as radiosensitizers of tumor tissue as well as radioprotectors of normal tissue [69]. Genistein is a nonspecific protein kinase inhibitor that acts as a scavenger REviEW Johnke, Sattler & Allison future science group for ROS [14].…”
Section: • • Naturally Occurring Antioxidantsmentioning
confidence: 98%
“…In mice, Hillman et al [62] investigated the role of soy isoflavones in the radiation protection of lung tissue. Histological examination of irradiated lungs revealed a chronic inflammatory infiltration involving the alveoli and bronchioles and a progressive increase in fibrosis.…”
Section: Reduction In Inflammationmentioning
confidence: 99%